Knowledge about COVID-19 among university students before the implementation of the enhanced community quarantine in Philippines - Jomell Miranda Santiago; Rita L. Cajucom (International Journal of Public Health Science (IJPHS), 2020)
The purpose of this study was to determine the knowledge of the students about Coronavirus Disease-2019 (COVID-19) before the Philippines government implements the enhanced community quarantine in Luzon. A descriptive research design was conducted among the students of Nueva Ecija University of Science and Technology, San Isidro Campus. The sample size was computed by using the Epi-Info version 2000 Computer Programme. Questionnaire was used to collect data that was composed of the profile, questions regarding their knowledge about COVID-19 and their source of knowledge. Permission to conduct and informed consent was obtained before the respondent answer the questionnaire. Data were analyzed using various statistical tools. Majority of the respondents had an average and good knowledge while sex was the only variable that differs significantly in their knowledge about COVID-19. Social media and seminars in the school were among their primary source of knowledge. It is concluded that students‟ knowledge about COVID-19 was sufficient. However, the absence of vaccines against COVID-19, prevention and control of the disease was the only way to fight it which requires organizing health education campaigns in different communities to disseminate more information on how everybody can effectively deal with this pandemic.